Triage options to manage high‐risk human papillomavirus‐positive women: A population‐based cross‐sectional study from rural China. Issue 8 (24th April 2020) - Rezhake, Remila; Chen, Feng; Hu, Shang‐Ying; Zhao, Xue‐Lian; Zhang, Xun; Cao, Jian; Qiao, You‐Lin; Zhao, Fang‐Hui; Arbyn, Marc
Abstract: Improvement in managing HPV‐positive women is urgently needed. Based on a population‐based study which included 2112 women aged 49 to 69 from Shanxi, China, we aimed to evaluate the clinical performance of multiple triage strategies based on liquid‐based cytology (LBC), p16 INK4a, viral load and partial genotyping, as a single or combined strategy for detecting cervical intraepithelial neoplasia grade 2/3 or higher (CIN2+/CIN3+) in women who tested positive by Hybrid Capture 2 (HC2). Among 452 HC2‐positive women, the test positivity of LBC (ASC‐US+), p16 INK4a, HPV16/18 and HPV16/18/31/33/45 were 39.6%, 38.5%, 18.0% and 40.0%, respectively. Compared to LBC (ASC‐US+) triage, a single triage strategies using p16 INK4a or extended genotyping (SureX HPV16/18/31/33/45) achieved comparable sensitivity (relative sensitivity: 1.08, 95% confidence interval [CI]: 0.93‐1.26 and 0.96, 95% CI: 0.76‐1.22) and specificity (relative specificity: 1.05, 95% CI: 0.96‐1.14 and 1.02, 95% CI: 0.92‐1.14) for CIN3+. Viral load triage using a ≥50 RLU/CO cut‐point also yielded similar results with LBC (ASC‐US+). Among combined triage strategies, HPV16/18 genotyping with reflex p16 INK4a showed higher sensitivity and slightly lower specificity than LBC (ASC‐US+) for CIN3+ detection, however, the differences were not statistically significant. Of note, after a negative result by p16 INK4a or LBC among HPV16/18 negative women, the posttest probability of CIN3+ was lower than 1%. Our study suggested that p16 INK4a, extended genotyping and increased viral load cut‐point could be promising alternatives to cytology triage. Combined triage algorithms of HPV16/18 with reflex p16 INK4a or cytology, if negative, are associated with the substantial low posttest risk sufficient to release women to next screening round. Abstract : What's new? Cytology triage is widely used to manage the care of women with positive human papillomavirus (HPV) results following HPV‐based screening. Challenges with cytology in low‐resource settings, however, has fueled the development of other triage strategies. Whether these strategies are superior to cytology remains unclear. In this population‐based evaluation, promising alternatives to cytology triage were identified, including p16 INK4a biomarker testing, extended genotyping, and viral load with increased cut‐point. These methods were especially suitable for settings that lack trained cytologists. Combined HPV16/18 with reflex p16 INK4a or cytology provided optimal risk stratification, enabling double‐negative cases to be released to routine screening.